NUMERICAL ANALYSIS OF MOUNTING BRACKET STRUCTURE ON THE DAMPING EFFECT OF STABILIZER STEERING DAMPERS - Wibowo, Muhammad Yusuf; Bahatmaka, Aldias; Rusiyanto, Rusiyanto; Fitriana, Deni Fajar; Ghyferi, Andi Abdullah; Anwar, Ahmad; Ridananda, Ayyub; Chasan, Ahmad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Due to bumps or holes in the road, certain regions' road surface is still unsuitable for riding at high speeds. Many motorcycles used stabilizer steering dampers to reduce weave and wobble. Bracket is a structure that holds the stabilizer steering dampers to the motorcycle steering. Bracket plays a significant role in maintaining the stabilizer steering dampers as well as stopping any vibration due to the dynamic conditions. This paper presents Finite Element Analysis of a bracket, which is analyzed material aluminum 6061 and aluminum alloy cast. In this study, we have explored using Static Analysis to calculate the internal force, displacement, and stress of structural brackets. Hence in this study, we have performed Modal Analysis to determine the natural frequencies of the bracket for safety. And also, we have performed Transient Analysis to study the behavior of structure brackets over time in response to time-varying loads and vibrations in dynamic conditions.